STUDI KUALITAS UDARA DI SEKITAR SUNGAI TELAGAWAJA, DESA MUNCAN, KABUPATEN KARANGASEM BALI - ARTHANA, I WAYAN (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2012)
The research was done in surrounding Telagawaja River at Muncan Village, Karangasem Regency, Bali at October 2008. The aim of the research was to know the air quality condition in that area. There were six air quality parameters measured at three different sites. The content of NO2 at the air varied 24,29-31,87 ?g/m3 was higher than that in Gunaksa Beach where there are no activities at all but it was lower than that in Sawangan Nusa Dua where full of tourism activities. The level of SO2 at the range of 34,44-44,97 ?g/m3 was lower than that in Padangbai Harbour where full of human activities and transportations. The content of dust at the range of 105,82 ?g/m3, CO at the range of 497,78-568,89 ?g/m3, Pb at the range of 0,250-0,792 ?g/m3. The level of noise at the range of 40,33-53,79 dB(A) was lower than that in village community at Kubu, Karangasem Regency and also lower than that in Sawangan Beach of Nusa Dua. All the air quality parameters are not yet over than standard of safe air quality level.
Keywords: air quality, nitrogen dioxide, sulfur dioxide, lead, dust, noise